Catalase activity of macromycete Pleurotus Ostreatus (JACQ.:FR.) P. Kumm. at the efect of laser irradiation - Reshetnyk, Kateryna; Yuskov, Dmytro (ScienceRise: Biological Science, 2019)
Enzyme catalase is characterized by the high catalytic activity, almost doesn’t need activation energy, reaction velocity of this enzyme limits not only the velocity of substrate diffusion to the active center. The action mechanism of catalase is in disintegration of hydrogen peroxide with emission of molecular oxygen. The enzyme is used as a component of biosensors for determining the quantitative content of hydrogen peroxide and ethanol. Aim of the work was to study the influence of laser radiation on the catalase activity of macromycete Pleurotus ostreatus (Jacq.:Fr.) P. Kumm.. Materials and methods. Irradiations of inolulum of always the same density and age were realized before inoculation using LED lasers of red, blue and green light with power 100 mWt. The catalase activity in mycelium and cultural filtrate was determined spectrophotometrically, based on the ability of hydrogen peroxide to form the stable colored complex with molybdenum salts. Results. The obtained results allow to make a conclusion about changeability of studied strains in the catalase activity of CF and MH. In particular, the highest index of catalase activity of cultural filtrate and mycelium homogenate was fixed for the strain Р - 191 of the fungus P. ostreatus. The worst producer of extracellular catalase is the strain Р - 108. The least value of the activity of mycelium catalase has been established for the strain Р - 192. It is probably explained by individual characteristics of these strains. Laser irradiation had a positive influence on the catalase activity of cultural filtrate and mycelium homogenate. Thus, in cultural filtrate the maximum catalase activity was fixed as a result of irradiation by the blue laser for the strain Р-191 of fungus P. ostreatus - 2986,72 ± 11,26 mcat / l. The catalase activity growth in mycelium homogenate has been established for the strain Р-192 also at the effect of blue laser irradiation - by 29,59%. Conclusions. It has been established, that laser irradiation by blue and green light with duration 10 s results in the catalase activity growth of cultural filtrate and mycelium homogenate of the studied strains of P. ostreatus. The effect of red light doesn’t cause reliable changes of the enzyme activity in most studied strains. The most reaction was inherent to the strains Р – 191 and Р - 192 of fungus P. ostreatus as a response to irradiation by blue light. Thus, the index of catalase activity of cultural filtrate for the strain Р - 191 grew by 20,18%, and the catalase activity of mycelium grew by 29,59% for the strain Р - 192. Other studied strains had less essential changes of the catalase function as a response to irradiation